Rationale for routine preoperative liver function tests before elective cholecystectomy (Journal of Patan Academy of Health Sciences, 2023)
Preoperative work-up before elective cholecystectomy often undergoes a range of routine investigations that includes liver function tests (LFTs). There is fear of concomitant common bile duct stones (CBDs) in patients with negative ultrasonography (USG) findings, i.e. with no dilatation of bile ducts or presence of stones in it or clinical features of hepatitis or jaundice. Studies show that clinical practice of preoperative workup of routine liver function tests for every elective cholecystectomy patient is questionable, possibly because of peer pressure or defensive medicine practices or simply a ‘copy-paste’ from the practices of seniors.1,2 Preoperative blanket tests on the pretext of ‘finding any abnormalities’ has poor scientific merits. The preoperative LFTs for uncomplicated, elective cholecystectomy patients rarely add value and do not alter the already planned decision based on symptomatology, history, physical examination, and ultrasound diagnosis of cholelithiasis. The clinical pathway for the management in most cases remains unchanged. The practice of menu-style routine tests adds to the cost and rarely adds further useful information sufficient enough to alter the planned clinical pathway.3